S-layers: The Proteinaceous Multifunctional Armors of Gram-Positive Pathogens - Ravi, Janani; Fioravanti, Antonella (Frontiers in Microbiology, 2021)
S-layers are self-assembled crystalline 2D lattices enclosing the cell envelopes of several bacteria and archaea. Despite their abundance, the landscape of S-layer structure and function remains a land of wonder. By virtue of their location, bacterial S-layers have been hypothesized to add structural stability to the cell envelope. In addition, S-layers are implicated in mediating cell-environment and cell-host interactions playing a key role in adhesion, cell growth, and division. Significant strides in the understanding of these bacterial cell envelope components were made possible by recent studies that have provided structural and functional insights on the critical S-layer and S-layer-associated proteins (SLPs and SLAPs), highlighting their roles in pathogenicity and their potential as therapeutic or vaccine targets. In this mini-review, we revisit the sequence-structure-function relationships of S-layers, SLPs, and SLAPs in Gram-positive pathogens, focusing on the best-studied classes, Bacilli (Bacillus anthracis) and Clostridia (Clostridioides difficile). We delineate the domains and their architectures in archetypal S-layer proteins across Gram-positive genera and reconcile them with experimental findings. Similarly, we highlight a few key ‘flavours’ of SLPs displayed by Gram-positive pathogens to assemble and support the bacterial S-layers. Together, these findings indicate that S-layers are excellent candidates for translational research (developing diagnostics, antibacterial therapeutics, and vaccines) since they display the three crucial characteristics: accessible location at the cell surface, abundance, and unique lineage-specific signatures.